2017
DOI: 10.2147/jep.s128696
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous administration of fluoxetine and simvastatin ameliorates lipid profile, improves brain level of neurotransmitters, and increases bioavailability of simvastatin

Abstract: Simvastatin (STT), a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, is widely prescribed for dyslipidemia, whereas fluoxetine (FLX) is the first-choice drug for the treatment of depression and anxiety. A recent report suggests that selective serotonin reuptake inhibitors can interact with the cytochrome P450 3A4 substrate, and another one suggests that STT enhances the antidepressant activity of FLX. However, the data are inconclusive. The present study was designed to explore the pharmacokinetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Endocytosis as a mechanism of desensitization of the serotonin 1A receptor has been implicated in the therapeutic action of popular antidepressants (SSRIs) such as fluoxetine. , Interestingly, recent cohort studies suggest that the combination of SSRIs and statins could have superior antidepressant effects relative to SSRI treatment alone. , In another study, the simultaneous administration of fluoxetine and statin has been suggested to enhance the levels of serotonin in rat brain . In this backdrop, our results on a cholesterol-induced switch in the endocytic and intracellular trafficking pathway of the serotonin 1A receptor assume significance.…”
Section: Discussionmentioning
confidence: 57%
“…Endocytosis as a mechanism of desensitization of the serotonin 1A receptor has been implicated in the therapeutic action of popular antidepressants (SSRIs) such as fluoxetine. , Interestingly, recent cohort studies suggest that the combination of SSRIs and statins could have superior antidepressant effects relative to SSRI treatment alone. , In another study, the simultaneous administration of fluoxetine and statin has been suggested to enhance the levels of serotonin in rat brain . In this backdrop, our results on a cholesterol-induced switch in the endocytic and intracellular trafficking pathway of the serotonin 1A receptor assume significance.…”
Section: Discussionmentioning
confidence: 57%
“…Whereas the potential interaction between fluoxetine and statins has not been investigated in humans, experimental evidence in animal models found that the combination of simvastatin with fluoxetine may result in a potentiation of the anxiolytic and antidepressant properties and produce convergent effects on different neurotransmitter systems or signalling targets in the brain . Based on these findings, Al‐Asmari and colleagues evaluated the PK and PD consequences of the combined administration of simvastatin and fluoxetine in experimental animals. Co‐administration of simvastatin with fluoxetine resulted in a significant increase in the bioavailability of simvastatin in the plasma (41.8%) and brain (68.7%) compared to administration of simvastatin alone ( P < .05).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, statins increase hippocampal serotonin levels ( 43 ), and induce serotonergic-dependent antidepressant-like effect that are counteracted by 5HT 1A and 5HT2 A/C receptor antagonists ( 63 ) and upregulate pre-frontal dopamine receptors expression ( 64 ) in animal models of depression. Moreover, statins seem to directly potentiate the serotonergic effects of some antidepressants in animals ( 65 67 ) and possibly in human trials ( 68 ). Non-monoaminergic pathways have also been explored in animal models of depression, showing that statins may elicit antidepressant action via opioid- ( 69 ) and endocannabinoid-mediated ( 70 ) neurotransmission.…”
Section: Introductionmentioning
confidence: 99%